FULL DAY SCHOOL ACTIVITIES FROM THE PERSPECTIVE OF HUMAN RIGHT AND ISLAMIC RELIGION - Dafid Ginting; Musran Munizu; Haidi Hajar Widagdo; Lailatul I’zaati; Alfina Wildatul Fitriyah (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The Full Day School policy is aimed at increasing student knowledge and character formation. However, in its implementation the policy has the potential to violate Human Rights and Islamic Law. Therefore, this research aims to analyze the Full Day School Activities Policy from a Human Rights perspective, especially regarding the part of social and cultural rights, namely the right to receive adequate and quality education and from an Islamic Law perspective, especially regarding one of Al-Maslahah Al- Khamsah is Hifz l-Nasl (Guarding the Offspring). This research is qualitative research with a descriptive approach, namely describing the Full Day School Policy from the perspective of Human Rights and Islamic Law. The data used in this research is secondary data collected using the library research method. The data collected was analyzed using the stages of observation, data selection, most appropriate reduction, and drawing conclusions. The research results show that the Full Day School policy can be in line with and hinder the implementation of human rights principles, especially regarding the right to receive good and quality education. This policy can also be in line with Al-Maslahah Al-Khamsah in special Islamic law regarding hfiz al-nasl (protecting offspring) provided that the policy is effective and able to provide knowledge for students, as well as shape student character. On the other hand, this policy can become an obstacle if it is not effective and is in vain. Keywords : Full Day School Activities, Human Right, Islamic Religion.